2020
DOI: 10.21203/rs.3.rs-67654/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards COVID-19 in Saudi Arabia: Planning implications for public health pandemics

Abstract: BackgroundSaudi Arabian authorities have implemented a number of preventive measures to confront COVID-19, including complete public lockdown, limitations on many services and a public awareness campaign. The success of these preventive measures is highly dependent on individuals’ compliance, which is influenced by their knowledge, attitudes and practices towards this disease. This study aims to assess the knowledge, attitudes and practices towards COVID-19 among the population of Saudi Arabia.MethodsThis is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In this study, majority of the participants washed their hands using alcohol-based sanitizers. Our results were similar to those of a previous study during early stages of the pandemic by Almalki, who reported that 96.7% of the participants washed their hands as recommended by the Ministry of Health ( 30 ). However, our results were slightly better than those of a more recent study by Battineni et al, who reported that ~94% of seafarers washed their hands by rubbing at least 20 s with the use of sanitizers ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, majority of the participants washed their hands using alcohol-based sanitizers. Our results were similar to those of a previous study during early stages of the pandemic by Almalki, who reported that 96.7% of the participants washed their hands as recommended by the Ministry of Health ( 30 ). However, our results were slightly better than those of a more recent study by Battineni et al, who reported that ~94% of seafarers washed their hands by rubbing at least 20 s with the use of sanitizers ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…(15) Mohammed J. Almalki mentioned in his study which was conducted in Saudi Arabia depicted that 77% respondents answered correctly to knowledge questionnaire and thereby inferred that Saudi population have adequate knowledge, good attitude and practices towards COVID 19. (16) Secondly in Figure 4, it was evident that the overall level of awareness of disease was around 64%. The other respondents are either not sure of answer asked in knowledge questionnaire.…”
Section: Discussionmentioning
confidence: 94%
“…These studies identified the general people's knowledge, attitude and practice on COVID‐19 in Saudi Arabia. 7 , 8 , 9 , 10 But to the best of authors' knowledge, no study has been reported which investigates the association of KAPs related to COVID‐19 KAPs among dental hygiene students in Kingdom of Saudi Arabia. Coronavirus (COVID‐19) is a new virus that has rapidly spread around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Various KAP studies have been performed on the population of Saudi Arabia. These studies identified the general people's knowledge, attitude and practice on COVID‐19 in Saudi Arabia 7–10 . But to the best of authors' knowledge, no study has been reported which investigates the association of KAPs related to COVID‐19 KAPs among dental hygiene students in Kingdom of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation